Social-psychological disadaptation and rehabilitation directions for the members of military families - A. Y. Kivorkova; A. G. Soloviev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
This review summarizes the results of studies which demonstrate the impact of chronic stress to the representatives of the extreme profile activities and social environment. In our work we show how family members can ensuring the normal professional functioning of servicemen; systematic data about the occurrence of social-psychological disadaptation of the family members. Based on the literature data and the results of our research, we identificated the risk factors of social-psychological disadaptation of the military wives which are situated in a social stressful situation during a long time. It is found that family members who have undergone medical and psychological rehabilitation, revealed a positive trend.